Об автоматизации проектирования технических устройств - Ивахненко, И. А.; Ивахненко, Т. Н. (НТУ "ХПИ", 2014)
В статье использован ранее предложенный авторами способ проектирования технических устройств (ТУ) для проектирования его варианта в состоянии «передавать теплоту от жидкости А жидкости Б». Изготовлена часть проекта, которая завершается простыми состояниями. Определены некоторые требования к математическому обеспечению предложенного способа.

On automation if designing technical devices. In this article the authors use offered formerly method of designing technical devices (TD) to design its option in condition: «transfer heat from liquid A to liquid B». Part of the design, which is made, concludes with simple condit ions. Defined are some requirements to mathematical programmes for the method of fered.
On automation of designing technical devices
Keywords: состояние; признак; схема отношения состояний; дерево состояний; математическое обеспечение; method of designing; technical device; condition; sign; condition tree; mathematical programmes